Tribute to a Law Teacher with a Heart and a Social Conscience - Palmer, Geoffrey (Victoria University of Wellington Law Review, 2015)
The author, having served as Professor at the Victoria University of Wellington Faculty of Law alongside him, provides a tribute to his colleague Professor Bill Atkin. The author commends Professor Atkin's role as an influential scholar and teacher in the somewhat incoherent area of family law, stating that Professor Atkin is an outstanding academic lawyer who has made a significant contribution to the improvement of the law in New Zealand.